hERG: protein trafficking and potential for therapy and drug side effects - Staudacher, Ingo; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (Current opinion in drug discovery & development, 2010)
Drug-induced QT interval prolongation is associated with torsade de pointes arrhythmia and sudden cardiac death. Acquired long QT syndrome poses a significant liability in pharmaceutical drug development, and has resulted in drugs being recalled from the market. This off-target property is caused primarily by the inhibition of cardiac hERG K+ currents. As a result, guidelines were established by The International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) requiring the preclinical evaluation of direct hERG channel blockade and QT prolongation. This review discusses established, as well as newly discovered and currently under-recognized, pro-arrhythmic mechanisms that are associated with hERG protein trafficking. Defective hERG trafficking is a research area of intensive scientific activity, and the implementation of screening for this type of hERG liability should be considered in order to improve the risk assessment and detection of drug-associated cardiotoxicity in safety pharmacology.